Understanding informal segregation : racial and spatial identities among the Indian minority of Mokopane - Shaker, Sahba (Department of Psychology, 2016)
South Africa is a melting pot and a meeting place for a multitude of "races", representing an optimal arena for understanding the psychology of contact and desegregation. This study focuses on the spatial arrangement of minority identities, through continued informal segregation, among the Indian minority of Mokopane. Drawing on 28 open-ended interviews, segregation is explored in everyday interactions and spaces. Working within a spatial-discursive framework, critical discourse analysis is employed, paired with a basic observational and descriptive analysis. Participants' discursive constructions overwhelmingly demonstrate patterns of informal segregation among the Indian minority community, within the micro-ecology of contact. Caught within a sandwiched or "buffer" identity, issues of space constantly inform negotiating conceptions of "Indianness". In mapping the dialogue of the Indian community, a story of the evolution of segregation emerges, creating a replication of internal divisions. This study ultimately demonstrates the need for a spatial-discursive orientation and a more "embodied" turn in our understanding of segregation.